SENGKETA PULAU KURIL ANTARA RUSIA DAN JEPANG DITINJAU DARI HUKUM INTERNASIONAL - Donny Tanaka Silalahi; Suhaidi Suhaidi; Arif Arif (Journal of USU International Law, 2014)
ABSTRACTJapan is one country that is quite influential in the Asia-Pacific because the Japanese have a tremendous economic power. Asia and even the world economy is almost dominated by the Japanese-made products such as electronic goods and automotive. However, despite having a fairly strong economic power, Japan is one country in the world that military power is dependent on other countries the United States. Formulation of the research problem is: How can the setting status of the islands of territory in international law. How does the conflict between Russia and the Kuril islands Japan. How Kuril Islands Dispute Resolution in International Law. This type of research used in this study is normative. Normative legal research is a research method that refers to the legal norms contained in laws and court decisions. The setting of the sovereignty and maritime jurisdiction in a comprehensive manner the efforts of the four 1958 Geneva Conventions governing the territorial sea and contiguous zone, fishing and conservation of living resources in the high seas, the continental shelf and the open sea. However, the range of the 1970 convention began to be considered no longer adequate and emerging demands to review the contents of the convention. Ownership of the Kuril Island conflict between Russia and Japan, the Kuril islands were taken over by the Soviet Union (the old name of Russia) between 28 August to 5 September 1945, after Japan surrendered unconditionally to the Allies on August 15. In 1951 the San Francisco Security Treaty stated that Japan must surrender all claim to the Kuril islands to the allies. This agreement also does not recognize the sovereignty of the Soviet Union. So the demands of the Soviet Union over the Kuril islands is also not the case. The Soviet Union finally use the results of Yalta agreement as a legal basis. Kuril Island dispute resolution according to international law, the Kuril Islands dispute between Japan and Russia are based on international law and the principles used in resolving disputes islands claimed by Japan, these solutions include: Arbitration, Settlement through the diplomatic track, the International Court Resolution through referendum Keywords: Dispute Kuril Islands, Russia, Japan